(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2014)
Among the duplication cysts of Gastro intestinal tract, Gastric duplication is rarer. Here we are reporting a case of gastric duplication cyst in a neonate. JCMCTA 2014 ; 25 (2) : 57-60